Infected Urachal Cyst in a Young Female: A Case Report (Bangladesh Journal of Urology, 2020)
The urachus is a tubular structure that is patent during gestation. The lumen normallycloses at about the twelfth week of gestation and obliterates completely. Patenturachal anomalies are usually detected in childhood2,3. In adults they occur veryrarely and the presentation and diagnosis may be occasionally challenging. Wepresent and discuss the case of an infected urachal cyst found in a 25 year oldfemale.Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.100-102